MAPPING GLOBAL RESEARCH TRENDS ON TAX HOLIDAY: A BIBLIOMETRIC ANALYSIS USING VOSVIEWER - Qoyyimah, Aimmatul; Andriani, Sri (STIE Jambatan Bulan, 2025)
This study aims to map the progress of scientific research on tax holiday policies by utilizing a bibliometric approach through VOSviewer software and a literature review method. Tax holidays are tax incentives provided by the government to attract investment, especially in national strategic sectors. By collecting 448 articles from 2019 to 2024 using Publish or Perish software and conducting metadata analysis with Mendeley and VOSviewer, this study managed to find six main clusters and twenty related topics related to tax holidays. In addition, the results of the literature review show a relationship between tax holidays, foreign direct investment (FDI), tax rates, and the provision of tax incentives. This study states that tax holidays can be an effective policy tool if designed as part of a comprehensive economic strategy supported by macroeconomic stability and legal certainty